Knowledge about our experience and distinguishing between possibilities - Matuszkiewicz, Maria (Hybris, 2017)
In my article I reconstruct the main threads of Robert Stalnaker’s book Our Knowledge of the Internal World, which focuses on the problem of our epistemic relation to our experience and the relation between experience and knowledge. First, the book proposes an interesting view of externalism, which combines classical externalist claims with a contextualist approach to content ascriptions. The approach accommodates some important internalist intuitions by showing how content ascriptions can be sensitive to the perspective from which a subject perceives the world. Second, Stalnaker proposes a theory of self-locating and phenomenal knowledge, which should be understood in terms of differentiating between real possibilities. The puzzling upshot of this elegant solution is that it commits one to the existence of possibilities accessible only from the first-person perspective. Finally, Stalnaker presents an argument which shows that our knowledge about our phenomenal experience is no more direct than the knowledge about external objects. Stalnaker’s claim that by merely having an experience we don’t learn any new information seems, however, too strict in light of his contextualist approach to content ascriptions.